Key Clinical Interest Outcomes of Pharmaceutical Administration for Veterans With Post-Traumatic Stress Disorder Based on Pooled Evidences of 36 Randomised Controlled Trials With 2,331 Adults - Zhao, Yi-Fan; Huang, Zhen-Dong; Gu, Hui-Yun; Guo, Guang-Ling; Yuan, Rui-Xia; Zhang, Chao (Frontiers in Pharmacology, 2020)
Background: The effects of drug treatment on veterans, who have a high risk of post-traumatic stress disorder (PTSD), are not clear, and the guidelines are different from the recommendations of the recent meta-analysis. Our goal was to find the efficacy and frequencies of complications of drugs that can treat PTSD in veterans. Method: We searched Ovid MEDLINE, Ovid Embase, The Cochrane Library and Web of Science until January 1, 2020. The outcomes were designed as the change of PTSD total scale, subsymptom score, response rate, frequencies of complications outcomes, and acceptability. Results: We included a total of 36 randomised controlled trials with a total of 2,331 adults. In terms of overall effect, drug treatment is more effective than placebo in change in total PTSD symptoms scale (SMD=-0.24, 95%CI [-0.42, -0.06]) and response (RR=1.66, 95%CI [1.01, 2.72]). However, in terms of frequencies of complications, drugs generally had a higher withdrawal rate (RR=1.02, 95%CI [0.86, 1.20]) and a higher frequencies of complications (RR=1.72, 95%CI [1.20, 2.47]) than placebo. Risperidone showed a good curative effect in change in total PTSD symptoms scale (SMD=-0.22, 95%CI [-0.43, 0.00]) and acceptability (RR=1.31, 95%CI [0.82, 2.59]). The drugs acting on 5-HT receptors, our results showed that symptoms of hyper-arousal (SMD=-0.54, 95%CI [-0.86, -0.21]), symptoms of re-experiencing (SMD=-0.62, 95%CI [-0.86, -0.39]) and symptoms of avoidance (SMD=-0.53, 95%CI [- 0.77,-0.3]), The drugs acting on dopamine receptors, our results showed that symptoms of re-experiencing (SMD=-0.35, 95%CI [-0.55, -0.16]) and the drugs acting on α2 receptor has a significant effect on reducing total PTSD symptoms scale (SMD=-0.34, 95%CI [-0.62, -0.06]). Conclusions: Drug therapy can effectively treat PTSD, but its frequencies of complications should be considered. Different from the guidelines for adult PTSD, this study supports atypical antipsychotics, selective serotonin reuptake inhibitors and receptors that act on 5-HT and dopamine for the treatment of PTSD in veterans. Based on evidence among these drugs, the risperidone is the most effective for veterans, otherwise, sertraline is used as an alternative.